Hydrological and Hydraulic Analysis of Drainage System of Salamanmloyo Sub-district, Semarang, Indonesia - Sarminingsih, Anik; Alma, Georgia; Nugraha, Winardi Dwi (Universitas Diponegoro, 2025)
Salamanmloyo, one of the sub-districts in West Semarang District, Semarang City, is a densely populated area with nearly all of its land built-up. Due to its location in the lower region of Semarang, it is vulnerable to flooding. Salamanmloyo has experienced floods and inundation due to insufficient pervious areas and inefficient drainage channels. This occurs when there is an imbalance between the drainage channel capacity and the discharge that needs to be handled, as well as when waste, sediment, and vegetation are present in the channel. As for the existing conditions in the Salamanmloyo Sub-district, no previous study regarding flooding and inundation has been conducted in this area. Therefore, it is necessary to conduct research and planning to determine the existing conditions of drainage channels, hydraulic and hydrological analysis results, and suitable SUDS types to decrease the flooding volume level. Hydraulic and hydrological analyses will be performed as a part of this planning, after which EPA SWMM 5.1 modelling will be performed under four different conditions: current, maximum SUDS application, channel normalization, and channel re-design conditions. The outcomes of the SUDS planning were applied in the form of 497 units of infiltration wells and 16,345.6 m2 of permeable pavement. SUDS implementation, drainage channel normalization, and redesign helped minimize the total flooding volume by 66.3%, from 231,456 m3 to 78,008 m3.